(untitled) (Research, Society and Development, 2020)
Syphilis in pregnant women persists in Brazil, between 2005 and June 2016, a total of 169,546 cases of syphilis in pregnant women was reported in the Information System for Notifiable Diseases, with a higher rate in the Southeast region 169,546 cases of syphilis in pregnant women, with a higher rate in the Southeast region. Failure to adequately treat syphilis can lead to an increase in the public health problem, with hospital admissions, public spending and an increase in the rate of congenital syphilis in Brazil. The objective of the work was to characterize the profile of pregnant women admitted to the Reception and Risk Classification sector. This is a quantitative, descriptive, cross-sectional study. Program R® version 3.5.1 was used. Statistical analysis of this article was carried out by making hypothesis tests to make reliable inferences, such as mathematically probable and making graphs to elucidate the distribution of variables. We chose to adopt 0.05 as the level of significance. As for the results and discussions, there was a higher incidence of pregnant women with syphilis in the age group between 20 and 29 years old, with schooling up to complete elementary school and black. The data analyzed in this research allowed to characterize the profile of women at the time of the diagnosis of syphilis with schooling, age, race, those who performed and did not perform prenatal care, and with which they did and did not undergo treatment. It is noticed that the lack of adherence to education has a strong influence on the lives of these women with regard to syphilis in pregnant women.